"The Difficult Step into Actuality": On the Makings of an Early Romantic Realism1. Issue 2 (3rd May 2016) - Frank, Manfred
ABSTRACT: Was the philosophy of Early German Romanticism, as we understand it today, nothing but a milder variety of Early German Idealism? Not at all! One has only to note the radical differences between the two. Friedrich von Hardenberg (who published under the pseudonym "Novalis") and Friedrich Schlegel, the two most significant thinkers of the Early Romantic movement, decisively broke with what Reinhold's critical disciples had called a "philosophy from the highest principle [ Grundsatzphilosophie ]." Instead of adopting Reinhold's and Fichte's idea of subjectivity as the principle of a deductively unfolding system of knowledge, they replaced it with the idea of "philosophy as an unending longing for the Infinite." Who only aspires to the Absolute cannot pretend to "possess" or capture it in an absolute knowledge as Fichte and Hegel did, but Schelling did not. Underlying Hegel's and Fichte's denial that the Absolute transcends knowability is the temptation to make existence itself dependent upon the grasp of thoughts or concepts, a temptation firmly rejected by the Early Romantics. This is why Early Romanticism should not be considered as a species of one or the other kind of Idealism, as most German and American researchers would like it to be.